BRIC agricultural policies through a WTO lens - Brink, Lars; Orden, David; Datz, Giselle (Wiley, 2013)
This article examines the agricultural policies of Brazil, Russia, India and China (BRIC) through the prism of the disciplines on agricultural domestic support in the World Trade Organization (WTO). Although the BRIC are often grouped collectively as an emerging force in the world economy, divergent agricultural interests are reflected in different approaches towards agricultural policy both through international dispute settlement and notification of their own support. We examine the support notified to the WTO for verification of compliance with their legal commitments, which under the complex WTO rules often differs significantly from measurement of support in economic terms. We note the resulting difficulties of these disciplines in establishing limits on trade‐distorting support. Implications of a Doha agreement are examined. Although the prospect of adoption of new Doha disciplines has become remote, the negotiated provisions are informative about the future policy space the BRIC sought to maintain. Russia’s domestic support commitments under its 2012 WTO accession extend the international disciplines but share the complexity of the other cases.